2022
DOI: 10.1128/msystems.01191-21
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Medication Alters Small Intestinal Motility and Microbiota Composition in Healthy Rats

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disorder and is known to be associated with altered gastrointestinal function and microbiota composition. We previously showed that the gut bacteria harboring tyrosine decarboxylase enzymes interfere with levodopa, the main treatment for PD (S. P. van Kessel, A. K. Frye, A. O. El-Gendy, M. Castejon, A. Keshavarzian, G. van Dijk, and S. El Aidy, Nat Commun 10:310, 2019).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 78 publications
1
14
1
Order By: Relevance
“…However, the drawback of oral administration lies in the unavoidable intestinal absorption of SCFAs, may be influenced by various factors including gastrointestinal symptoms in patients with PD, dysbiosis of the intestinal microbiota, or drug interference, thereby affecting their absorption rate. [138][139][140] Furthermore, sustained or periodic intravenous infusion of SCFAs may lead to side effects such as venous inflammation. [141] Another approach involves enhancing dietary patterns, such as structuring a high dietary fiber intake, to promote anaerobic fermentation of dietary fiber by gut microbiota and generate SCFAs.…”
Section: Therapeutic Implications Of Scfas For Pd Managementmentioning
confidence: 99%
“…However, the drawback of oral administration lies in the unavoidable intestinal absorption of SCFAs, may be influenced by various factors including gastrointestinal symptoms in patients with PD, dysbiosis of the intestinal microbiota, or drug interference, thereby affecting their absorption rate. [138][139][140] Furthermore, sustained or periodic intravenous infusion of SCFAs may lead to side effects such as venous inflammation. [141] Another approach involves enhancing dietary patterns, such as structuring a high dietary fiber intake, to promote anaerobic fermentation of dietary fiber by gut microbiota and generate SCFAs.…”
Section: Therapeutic Implications Of Scfas For Pd Managementmentioning
confidence: 99%
“…Of note, this study demonstrated that bacterial function could shift in response to drugs without a change in taxon abundance, thus highlighting the need for using metrics other than abundance when investigating the impact of drugs. Importantly, the interaction between the microbiome and drugs is bidirectional, with many studies clearly demonstrating that gut microbes can also actively metabolize 9,10,11,12 , and under certain circumstances bioaccumulate 13 , pharmaceutical drugs. While several studies to date have shed light on the nature and extent of microbe-driven drug transformations 9,10,11 , mechanistic details for human-targeted drug impact on the microbiome remain to be elucidated.…”
Section: Mainmentioning
confidence: 99%
“…The authors proposed that one mechanism that may explain the delay in gastric emptying in this population was the effect of levodopa on dopaminergic receptors in the stomach and that this might be exacerbated by the use of a dopa decarboxylase inhibitor, which would increase levodopa concentrations further, resulting in an effect on drug delivery and efficacy. A study in healthy rats showed that dopamine agonist treatment resulted in a reduction in small intestinal motility and an increase in bacterial overgrowth in the distal small intestine ( van Kessel et al, 2022 ). There was also an increase in the amount of small bowel bacteria ( Lactobacillus species), which correlated negatively with levodopa levels in the systemic circulation, suggesting an effect on the bioavailability of levodopa.…”
Section: Gastroparesis In Parkinson’s Diseasementioning
confidence: 99%